Molière, the French Revolution, and the theatrical afterlife - Leon, Mechele, 1958- (Studies in theatre history and culture., 2009)
From 1680 until the French Revolution, when legislation abolished restrictions on theatrical enterprise, a single theatre held sole proprietorship of Molière's works. After 1791, his plays were performed in new theatres all over Paris by new actors, before audiences new to his works. Both his plays and his image took on new dimensions. In Molière, the French Revolution, and the Theatrical Afterlife, Mechele Leon convincingly demonstrates how revolutionaries challenged the ties that bound this preeminent seventeenth-century comic playwright to the Old Regime and provided him with a place of hon.